Implementation of E-Dikmas by the Malang Police Traffic Unit in Preventing Traffic Accidents (Advances in Police Science Research Journal, 2024)
Traffic accidents have always been a serious issue within the jurisdiction of the Malang Police. One of the efforts by the Kamsel Unit of the Malang Police Traffic Division to address this problem is through public education in the field of traffic, based on electronic platforms (e-dikmas lantas). E-dikmas lantas is part of the strategies of the Kamsel Unit to "Develop superior human resources in the Police 4.0 era" and "Adapt to modern policing technology in the Police 4.0 era," as outlined in the 16 priority programs of the National Police Chief under the concept of precision policing (predictive, responsible, and transparent policing). This writing aims to describe the available organizational resources and the technology adoption undertaken in the implementation of e-dikmas lantas. Theories and concepts used include organizational resource theory (6M), technology adoption theory, implementation concepts, e-dikmas lantas concepts, and traffic accident prevention concepts. The study uses qualitative methods, with data sources from interviews, observations, and document studies. Triangulation techniques used are source and technique triangulation. Data analysis techniques involve data reduction, abstraction, data presentation, and conclusion drawing. The results indicate that the existing organizational resources are not yet optimal, particularly in terms of man, money, and market. Regarding the technology adoption, the implementation of e-dikmas lantas is operationally, financially, and technically feasible. However, it has not yet significantly reduced the number of traffic accidents. Based on these findings, it is recommended that future research focuses on the effectiveness of e-dikmas lantas in preventing traffic accidents. It is also suggested that the Kamsel Unit of the Malang Police Traffic Division expands e-dikmas lantas to various public service centers, conducts training for members in multimedia and graphic design, and improves budget management by monetizing social media accounts, especially YouTube, to generate additional income for operational purposes.
Keywords: Kata Kunci : E-Dikmas Lantas, Unit Kamsel, Adopsi Teknologi